Control strategy of novel hybrid commutated converter based on reverse blocking integrated gate commutated thyristor for commutation failure mitigation - Zongze Wang; Zhanqing Yu; Lu Qu; Zhichang Yuan; Kangsheng Cui; Jian Shi; Biao Zhao; Rong Zeng (High Voltage, 2025)
Abstract Commutation failure (CF) is an inherent problem faced by line commutated converter high voltage direct current (LCC‐HVDC) technology. To completely solve the problem of CF, we have proposed a novel hybrid commutated converter (HCC) technology based on reverse blocking integrated gate commutated thyristor, which can utilise two methods for commutation: enhanced grid voltage commutation and active turn‐off forced commutation. In this paper, the topology and operating principle of HCC are proposed. Then, the control and protection strategy is designed based on the current variation trend under AC faults. To verify the effectiveness of HCC in mitigating CF, a 120‐kV/360‐MW HCC‐HVDC model is built in PSCAD/EMTDC, adopting LCC at the rectifier side and HCC at the inverter side. Based on this model, HCC steady‐state and fault transient stresses are analysed. Various AC faults are simulated and the performance of HCC‐HVDC is compared with LCC‐HVDC. Finally, the results show that the HCC topology and proposed control strategy can solve CF under all fault conditions with almost the same attributes as LCC, such as large capacity, low cost, low loss and high reliability, which is meaningful for the application of HCC to the HVDC transmission system.